Hybrid Materials Based on Carbon Nanotubes and Nanofibers for Environmental Applications - Navrotskaya, Anastasiya G.; Aleksandrova, Darya D.; Krivoshapkina, Elena F.; Sillanpää, Mika; Krivoshapkin, Pavel V. (Frontiers in Chemistry, 2020)
With the advances in material science, hybrid nanomaterials with unique mechanical, electrical, thermal and optical characteristics have been developed. Among them, hybrids based on filamentous forms of carbon, such as carbon nanotubes and carbon nanofibers, in combination with inorganic nanoparticles attract particular attention. Due to the structure and morphology, charge and energy transfer processes lead to synergistic effects that allow the use of less material with higher productivity. To clarify these issues, this review will summarize and discuss the relevant studies of the use of inorganic compounds of various chemical groups in modifying carbon nanomaterials for ecological applications.